CONTENT, FORMS AND METHODS OF FORMING TECHNOLOGICAL COMPETENCE STUDENTS OF TEACHING PROFESSIONS - Kuzemko, Lesya V. (Educological discourse, 2015)
The article describes the basic knowledge and practical skills that make up the structure of the technological competence of the teacher and ensure efective implementation of vocational and educational activities; disclosed the purpose, content, methods of teaching students of teaching professions, contributing to the formation of the technological competence of future specialist; presents semantic units of the course «New educational technology training», practical tasks and tasks for independent work that orient future teachers to develop their own innovative profession strategies.